HajjLocator: a hajj pilgrimage tracking framework in crowded ubiquitous environment - Mantoro, Teddy; Jaafar, Abi Dzar; Aris, Mohd Fadhli Md.; Ayu, Media Anugerah (2011)
Hajj, an annual Muslim pilgrimage, is one of the pillars of Islam and every able Muslim must perform this act at least once in their lifetime. During the pilgrimage, millions of Muslims from all over the world congregate for religious rituals in Makkah, Kingdom of Saudi Arabia. The cases of missing Hajj pilgrims are not uncommon and although several tracking and navigation devices have been introduced, there is still a need for a better solution in overcoming the issue. There are several factors that prevent a widespread use of the system, such as the operational costs, availability of the connections and the use in uncommon platform. Thus, this paper proposes a HajjLocator framework for Hajj Pilgrim tracking based on mobile phone environments as it is reasonably affordable and is extensively used by people. The prototype of HajjLocator, as a system to track and monitor pilgrims while performing Hajj, is also discussed.